POLITIK REGIONALISME DAN TANTANGAN ASEAN DI TENGAH ARUS BESAR GLOBALISASI - Budi Winarno (SPEKTRUM, 2008)
AbstractThe Regional international relation recently has been the other trend on global politics economy. Although the experts don’t have any compromise of how regionalism raises and beingtrend on international relation, either realism, liberal also structuralism. On their development regional cooperation dynamic couldn’t apart from economic globalization. ASEAN cooperation doesn’t enough for pressure economic integration and intra regional trade. That is happened because of loss political will and socialization between the members to private sectors. So ASEAN must prepare themselves, conflict resolution must build consensus building when ASEAN must meet many regional and global power. Keywords : regional cooperation, loss political will, conflict resolution